Meningkatkan Motivasi Belajar Peserta Didik melalui Kompetensi Dasar Penguatan Pemberian Reward di Kelas VII.2 SMPN 33 Palembang - Ainun Marhamah; Nyimas Nuria Hasna Anggraeni; Umi Chotimah (FKIP, Universitas Palangka Raya, 2024)
This research was conducted using classroom action research to improve the quality of the learning process by increasing the low learning motivation of class VII 2 students at SMP Negeri 33 Palembang through providing reinforcement to students. The research method uses descriptive methods with percentages to obtain data. Researchers conducted observations on 30 students assisted by colleagues. The calculation results show that students' learning motivation in pre-cycle activities is only 45% with a rating of not good, therefore, to increase learning motivation in cycle 1, try to give rewards in the quite good category, namely 68%. , cycle 2 increased with good criteria, namely 79% and cycle 3 also experienced an increase with a very good predicate with a percentage of 89%. So with the percentage obtained in the third cycle having exceeded the target set by the author in this PTK, the author concludes that PTK increases learning motivation by strengthening the provision of rewards with the help of the TaRL approach and quiz technology evaluation media can improve students' learning abilities. motivation to learn.